The Effect of the Use of Canva Application Learning Media on the Creativity of Students in Language Studio Extracurricular Activities at SMPN 1 Tanjung Emas - Deni Putri Sartika; Vevi Sunarti (Universitas Negeri Padang, 2021)
This research is motivated by the low creativity of students in language studio extracurricular activities at SMPN 1 Tanjung Emas. This condition is thought to be due to factors that influence the low creativity of students, one of the factors that is thought to greatly influence is the use of learning media that is less effective and efficient. This study aims to see the creativity of students through the use of Canva application learning media in language studio extracurricular activities at SMPN 1 Tanjung Emas. This type of research is using a quantitative approach to the quasi-experimental method (Quasi Experiment). The population in this study were students in the language studio extracurricular activities at SMPN 1 Tanjung Emas as many as 25 students, all of whom became the research sample. By using data analysis using the test formula paired sample t-test. From the data processing, it can be concluded that there is a significant difference between the creativity of students before being given an action (pretest) and after being given an action (posttest) using the Canva application learning media in the language studio extracurricular activities at SMPN 1 Tanjung Emas. Suggestions and results of this research are for educators to be able to further increase the creativity of students in using the Canva application learning media and for school principals at SMPN 1 Tanjung Emas as leaders at the school so that they can further increase the availability of facilities and infrastructure, especially effective and efficient learning media. as well as to support the creativity of students